Pathological and therapeutic aspects of matrix metalloproteinases: Implications in osteosarcoma. Issue 4 (20th May 2019) - Tang, Huayan; Tang, Zhaohui; Jiang, Yongjun; Wei, Weisheng; Lu, Jian
Abstract: Osteosarcoma (OS) is one of the most common malignant bone tumors in children and adolescents, and the eighth leading form of childhood cancer. Matrix metalloproteinases (MMPs) are proteolytic enzymes implicated in certain cancers including OS. In this review, we discuss the mechanism of actions of MMPs in progression of OS, and the therapeutic use of MMPs inhibitors in the treatment of OS with subsequent clinical studies and future management. The expression of MMPs is upregulated in cancer cells by a variety of cytokines and growth factors, and upregulation of MMPs induces degradation of the extracellular matrix that contributes to cell proliferation by releasing growth factors. MMPs promote the detachment and migration of endothelial cells, cross the basement membrane as well as invade the surrounding lymphatic vessels and causes cancer metastasis. The use of selective MMP inhibitors with limited side effects might be promising therapeutic strategy in the treatment of OS. More clinical trials are necessary to evaluate the role of selective MMPs inhibitors in the prevention and treatment of OS along with their assessment of toxicity.